Penegakan Hukum oleh Jaksa Penuntut Umum terhadap Remaja sebagai Residivis Pelaku Pemerkosaan di Kabupaten Nagan Raya - Elly Yuslisa; Phoenna Ath Thariq (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The crime of rape is a very serious problem, a crime that is rampant today is the crime of rape against minors. In this research, the type of research used is the Juridical Empirical approach. The research location used as a place to conduct research is the Nagan Raya District Attorney's Office. Because Aceh is a special Autonomous Region and refers to the Lex Specialis Derogat Legi Generali principle, which is a special law that overrides general law, in carrying out the prosecution of this case it will be charged with Aceh Qanun Number 6 of 2014 concerning Jinayat Law. Law enforcement carried out by the Public Prosecutor must provide benefits or be efficient for the community to achieve justice. But of course there is a difference in treatment between adults and children in terms of dealing with the law. There are several factors for the occurrence of criminal acts such as factors that arise from within the individual. Crime occurs not only from factors within the perpetrator's personal self but also from factors from outside the perpetrator such as family environmental factors, and community environmental factors.